Impacts of mineral resources: Evidence from county economies in China. (January 2020) - He, Xiaoping; Mou, Dunguo
Abstract: the literature proposes that a booming minerals sector leads to a development curse. The mineral markets in China experienced a prolonged boom over the period of 2000–2010. We empirically examine the effects of mineral resources on employment in county economies during the boom. We consider the endogeneity of the resource measure and employ an instrumental variables approach to resolve the problem. We find the mining boom exerts a significant "crowding out" effect on the manufacturing employment in mineral-resource-dependent counties, but benefits the employment in services. Because the increase in mining employment is sizeable in a mining boom, the overall employment in the resource-dependent counties has shown a small growth. These results are robust to alternative samples. Our findings confirm the argument that resource booms undermine manufacturing sectors through deindustrialization effects, though little evidence shows the existence of a resource curse in overall employment. We conclude that for a developing economy with rich mineral resources and a large population, it would be hard to following the road of industrialization relying on manufacturing. Highlights: Impacts of mineral resource dependence on local employment are investigated. Resource abundance is distinguished from resource dependence. The IV method is employed to address the endogeneity problem. The resource curse works for manufacturing employment. Non-manufacturing employment benefits from a mining boom.